Human Pregnancy Resources. Issue 4 (1st October 2016) - Gamble, Alyson
ABSTRACT: The Interactive Web column reviews freely available Internet resources that are interactive in some form and/or provide helpful videos and animations. The websites are used for assignments, lectures, and self-study purposes and are available for viewing within The Interactive Web blog at https://thewebisinteractive.wordpress.com/. For information on how to search the blog, please see the About, How to Search, Writing Opportunity, and Disclaimer webpage within the blog. Each of the favorite websites of users is labeled with a star. This issue will highlight pregnancy websites.